Le partage de l’eau dans l’oasis de Figuig (Maroc oriental) - Tariq Madani (Mélanges de la Casa de Velázquez, 2006)
The water complex of the Figuig oasis is a good example of the transformations wrought by man on his environment in response to the constraints of hostile and arid surroundings. Following a brief introduction on research into oases and the documentation available, this article seeks to reconstruct the process whereby Figuig became inhabited, and also to highlight the close links between that process, modes of water sharing and social codes. Water distribution was assured by a complex network ; this was fed by drainage galleries (ifli-s) and springs and composed of manifold sāqiya-s and storage and regulating pools. Sharing was based upon two units of measurement, one of time and one of volume. At Figuig, water rights were generally private property (milk) ; ownership could change hands in the same way as any piece of immovable property. And finally, irrigation rights proper were subject to a number of customary easements.